Promoting justice by treating people unequally: an experimental study - Alice Becker; Luis M. Miller (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Which inequalities among individuals are considered unjust? This paper reports the results of an experiment designed to study distributive choices dealing with arbitrarily unequal initial endowments. In a three-person distribution problem where subjects either know or do not know their endowments, we find impartial behavior to be a stable pattern. Subjects either compensate for initial inequalities fully or not at all in both conditions, and they do so more often when they do not know their endowment than when they know it. Moreover, the type and the size of the good to be distributed also affect the frequency of impartial behavior.
Keywords: C72; C92; 330; Veil of ignorance; impartial behavior; distributive justice; procedural fairness; Einkommensumverteilung; Spieltheorie; Test; Verteilungsgerechtigkeit; Rawls-Gerechtigkeitstheorie